Moral compass for young people (second edition) - Rafi, Muhammad (Paramount Books (Pvt.) Ltd; Pakistan, 2010)
Developed out of necessity after observing the state of today's youth, this exciting new book aims at building and instilling positive moral character in young people around the world. It discusses and explains one moral quality at a time and supports its arguments with the help of stories that teach lessons. This book is ideal for parents to read with their children, for schools to include in their syllabus, and for the younger generation around the world that lacks inspiration and seeks goodness and guidance towards the right path. Moral and ethics guide is embellished with true and fabled stories with captivating illustrations.